Bacterial biofilm in adenoids of children with chronic otitis media. Part I: a case control study of prevalence of biofilms in adenoids, risk factors and middle ear biofilms. (3rd April 2019) - Kania, Romain; Vironneau, Pierre; Dang, Huong; Bercot, Béatrice; Cambau, Emmanuelle; Verillaud, Benjamin; Camous, Domitille; Lamers, Gerda; Herman, Philippe; Vicaut, Eric; Tessier, Natacha; Van Den Abbeele, Thierry
Abstract: Background: Biofilms are communities of bacteria embedded in a self-produced glycocalyx matrix. Adenoids have been shown to harbor bacterial biofilms. Aim/objectives: To compare the prevalence of biofilms in adenoid of children with chronic otitis media (COM) (group1) versus a control group without any COM (group 2) having adenoids removed because of hypertrophy. Material and methods: One hundred and three children were prospectively enrolled in this case-control study, group 1 ( n = 52) and group 2 ( n = 51). The main outcome measurement was the prevalence of biofilm in adenoidectomy specimens analyzed using confocal laser scanning microscopy. Children in group 1 who had middle ear (ME) effusion and requiring the insertion of a tympanostomy tube underwent biopsy of the ME mucosa and effusion sampling. Results: Biofilms were found in adenoids' specimens of both groups and in the ME biopsy and effusion. The biofilm prevalence in adenoids was 63.5% (33/52) in group 1 and 47.1% (24/51) in group 2. Day nursery and previous antibiotics intake were significantly more frequent in group 1 than in group 2. Conclusions and significance: This case-control study demonstrates that adenoid tissue in children with COM contains more mucosal biofilms than adenoid tissue removed for hypertrophy. Biofilm was seen in ME biopsies and effusion.